EMPOWERMENT OF MSMEs AN EFFORT TO FULFILL THE MAQASHID SYARIAH ASPECTS THROUGH THE AGRARIAN REFORM ACCESS PROGRAM - Ahmad Deni Faisal; Nikmatul Masruroh; Moch. Chotib (Adisam Publisher, 2025)
The agrarian reform access program was launched by the National Land Agency (BPN) has been able to make MSMEs have more capital than before the program. So, the objectives of this study are, first, to explore the process of empowering MSMEs through the agrarian reform access program, second, the formulation of fulfilling the maqashid sharia aspect through the agrarian reform access program in empowering MSMEs. This study used a qualitative approach with a case study type on various MSMEs that received the agrarian reform access program. Data were collected using interview, observation, and documentation techniques. Data were analyzed descriptively with the interactive model stages from Miles and Huberman. Data validity uses source triangulation and technique triangulation. The results of the study stated that the MSME empowerment process was carried out with the stage of discovering strengths by building more partnerships, being able to build MSME dreams to be competitive, designing activities and determining activities. Second, the maqashid sharia aspect is realized through halal certification carried out by MSMEs so that it can increase sales profits and have an impact on increasing MSME income.